Zeolite‐Based Organic Synthesis (ZeoBOS) of Acortatarin A: First Total Synthesis Based on Native and Metal‐Doped Zeolite‐Catalyzed Steps. Issue 7 (16th January 2017) - Wimmer, Eric; Borghèse, Sophie; Blanc, Aurélien; Bénéteau, Valérie; Pale, Patrick
Abstract: Similarly to polymer‐supported assisted synthesis (PSAS), organic synthesis could be envisaged being performed by using zeolites, native or metal‐doped, as heterogeneous catalysts. To illustrate this unprecedented Zeolite‐Based Organic Synthesis (ZeoBOS), the total synthesis of acortatarin A was achieved through a novel strategy and using five out of eleven synthetic steps catalyzed by H‐ or metal‐doped zeolites as catalysts. Notably, the formation of an yne‐pyrrole intermediate with a copper‐doped zeolite and the spiroketalization of an alkyne diol with a silver‐doped zeolite have been developed as key steps of the synthesis. Abstract : A new concept, that is, Zeolite‐Based Organic Synthesis (ZeoBOS), is described for the efficient access to structurally complex and functionalized molecules and illustrated with the total synthesis of acortatarin A, a unique antioxidant natural product. The synthesis was achieved through a novel strategy, based on several synthetic steps catalyzed by H‐ or metal‐doped zeolites as catalysts.